EGb761, an extract of Ginkgo biloba leaves, reduces insulin resistance in a high-fat-fed mouse model - Wei-na Cong; Rong-ya Tao; Jin-ying Tian; Jiong Zhao; Qian Liu; Fei Ye (Elsevier, 2011)
EGb761, a standardized and well-defined product extract of Ginkgo biloba leaves, has beneficial effects on the treatment of multiple diseases, including diabetes and dyslipidemia. However, it is still unclear whether EGb761 can increase insulin sensitivity. The objectives of the present study are to evaluate the effects of EGb761 on insulin sensitivity in an obese and insulin-resistant mouse model, established through chronic feeding of C57BL/6J mice with a high-fat diet (HFD), and to explore potential mechanisms. Mice fed with HFD for 18 weeks (starting from 4 weeks of age) developed obesity, dyslipidemia (as indicated by biochemical measurements of blood glucose, triglyceride (TG), total cholesterol (TC), and free fatty acids (FFA)), and insulin resistance (as determined by the oral glucose tolerance test (OGTT) and the homeostasis model assessment of insulin resistance (HOMA-IR) index), compared to control mice fed with a standard laboratory chow. Oral treatment of the HFD-fed mice with EGb761, at low (100 mg/kg), medium (200 mg/kg), or high (400 mg/kg) doses, via oral gavage (once daily) for 8 weeks (starting from 26 weeks of age) dose-dependently enhanced glucose tolerance in OGTT, and decreased both the insulin levels (by 29%, 55%, and 70%, respectively), and the HOMA-IR index values (by 50%, 69%, and 80%, respectively). EGb761 treatment also ameliorated HFD-induced obesity, dyslipidemia, and liver injury, as indicated by decreases in body weight (by 4%, 11%, and 16%, respectively), blood TC levels (by 23%, 32%, and 37%, respectively), blood TG levels (by 17%, 23%, and 33%, respectively), blood FAA levels (by 35%, 38%, and 46%, respectively), and liver index (liver weight/body weight) values (by 12.8%, 25%, and 28%, respectively) in the low, medium, and high EGb761 dose groups, respectively. In further mechanism studies, EGb761 was found to protect hepatic insulin receptor β and insulin receptor substrate 1 from HFD-induced degradation, and to keep the AMP-activated protein kinase, which plays a crucial role in reducing lipotoxicity, from HFD-induced inactivation. We conclude that EGb761 can effectively reduce HFD-induced insulin resistance and ameliorate other symptoms of the metabolic syndrome.